(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
Protein loops are frequently considered as critical determinants that influence not only the function but also the structure of a protein. Bacillus lehensis G1 ClpC (WT) has a four-residue insertion at the ɑ4-β2 loop, which is absent in Bacillus subtillis ClpC. To foster a deep understanding of the significance of additional residues in the structure and function of ClpC, a deletion mutation involving residues 76-79 (∆76-79) was constructed. Circular dichroism spectroscopy was used to evaluate the structural perturbations associated with the deletion. The results demonstrated that, the precise configuration of the ɑ4-β2 loop is important for maintaining the structure and function of WT. ∆76-79 leads to severe global destabilisation and unfolding of the secondary structure of the protein, which decreases ATPase activity. The optimum temperature for ∆76-79 is 25 °C, down from 45 °C for WT. The results suggest that the additional four residues at the ɑ4-β2 loop are critical for WT’s structure and function.